2015
DOI: 10.1002/adsc.201500384
|View full text |Cite
|
Sign up to set email alerts
|

Easy, Green and Safe Carbonylation Reactions through Zeolite‐Catalyzed Carbon Monoxide Production from Formic Acid

Abstract: Zeolites with the right shape and acid site density and strength, such as certain ZSM-5f orms, were able to cleanly decompose formic acid to carbon monoxide (CO), and the latter could be directly used in palladium-catalyzed carbonylation reactions.As imple two-reactors ystem was designed to produce CO convenientlya nd then furtherr eactt his gas in as afe way.T he two-reactor systemi sp articu-larly cheap,e asy to set up and use.I na ddition, the carbonylation conditions without pressure allowed for very effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 60 publications
0
13
2
Order By: Relevance
“…With respect to the latter, Losch et al. have recently reported an easy and green carbonylation technology involving CO generated in situ upon the decomposition of FA over Brønsted acidic H–ZSM‐5 zeolite at mild conditions …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the latter, Losch et al. have recently reported an easy and green carbonylation technology involving CO generated in situ upon the decomposition of FA over Brønsted acidic H–ZSM‐5 zeolite at mild conditions …”
Section: Introductionmentioning
confidence: 99%
“…[7] With respect to the latter,L osch et al have recently reported an easy and green carbonylation technology involving CO generatedi nsitu upon the decomposition of FA over Brønsted acidic H-ZSM-5 zeolite at mild conditions. [8] Another route involves the direct hydrogenation of CO 2 with H 2 without prior CO 2 dissociation. This reaction is central to at echnology for H 2 storage in the form of al iquid fuel.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the aminocarbonylation reaction of 5‐iodo‐1,2,3‐triazole with secondary ( 2p–q ) and aromatic amines ( 2r ), such as diethylamine, piperidine and aniline did not furnish the aminocarbonylation products. According to literature the steric as well electronic effects in these amines, contribute to decrease the nucleophilicity, hamper thus the coordination ability of these substrates to palladium . In sequence, we focused our attention on the aminocarbonylation of 1,4‐disubstituted‐5‐iodo‐1,2,3‐triazoles (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Catalytic strategies are scarce. These involve zeolite‐based catalysts able to decompose FA at high temperatures (>150 °C), to remove water, and exhibit modest activity with turnover frequencies up to 39 h −1 . Very recently, while exploring the alkoxycarbonylation of alkenes with FA, Beller et al.…”
Section: Methodsmentioning
confidence: 99%
“…[12] Catalytic strategies are scarce.T hese involve zeolite-based catalysts able to decompose FA at high temperatures (> 150 8 8C), to remove water, and exhibit modest activity with turnover frequencies up to 39 h À1 . [13] Very recently,while exploring the alkoxycarbonylation of alkenes with FA,Beller et al discovered that palladium complexes,s upported by chelating bis-phosphines decorated with pyridine bases,could catalyze the acceptorless decarbonylation of FA. [14] Because the dehydrogenation of HCOOH is facile,b oth thermodynamically and kinetically,t he authors noted the concomitant release of at least 10 %C O 2 and H 2 .I nt he pursuit of ap ractical system able to selectively decarbonylate FA,w e sought atransition-metal-free method.…”
mentioning
confidence: 99%